Novel rapid synthesis of zinc oxide nanotubes via hydrothermal technique and antibacterial properties - Aal, Nadia Abdel; Al-Hazmi, Faten; Al-Ghamdi, Ahmed A.; Al-Ghamdi, Attieh A.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2015)
ZnO nanotubes with the wurtzite structure have been successfully synthesized via simple hydrothermal solution route using zinc nitrate, urea and KOH for the first time. The structural, compositions and morphology architectures of the as synthesized ZnO nanotubes was performed using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDS) and high resolution transmission scanning electron microscopy (HRTEM). TEM showed that ZnO nanotubes exhibited a wall thickness of less than 2 nm, with an average diameter of 17 nm and the length is 2 lam. In addition, the antibacterial activity of ZnO nanotubes was carried out in vitro against two kinds of bacteria: gram - negative bacteria (G -ve) i.e. Escherichia coli (E. coli) and gram - positive bacteria (G +ve) i.e. Staphylococcus aureus. Therefore, this work demonstrates that simply synthesized ZnO nanotubes have excellent potencies, being ideal antibacterial agents for many biomedical applications. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: ZnO; Nanotubes; Hydrothermal; Antibacterial properties